2007
DOI: 10.2176/nmc.47.453
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Nationwide Survey on Treatment and Outcomes of Congenital Hydrocephalus in Japan

Abstract: A nationwide questionnaire survey of congenital hydrocephalus in 2000 investigated the treatment and clinical outcomes for congenital hydrocephalus in Japan to evaluate the factors influencing clinical outcome. Surgical treatment was performed in 341 of 380 patients who survived the early neonatal period. Of 321 patients who had shunt operations, 295 (91.9%) underwent ventriculoperitoneal shunting and nine (2.8%) ventriculoatrial shunting. Programmable valves were used in 83 (33.6%) of the 247 patients at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…This late detection and delayed shunting might have been responsible for the poor prognosis. Other studies have also showed a better outcome in patients who were shunted earlier than those who underwent late shunt surgery [9,10,11]. In this study, 66.66% of cases had aqueductal stenosis on the computerized axial tomography brain scan [12].…”
Section: Discussionsupporting
confidence: 51%
“…This late detection and delayed shunting might have been responsible for the poor prognosis. Other studies have also showed a better outcome in patients who were shunted earlier than those who underwent late shunt surgery [9,10,11]. In this study, 66.66% of cases had aqueductal stenosis on the computerized axial tomography brain scan [12].…”
Section: Discussionsupporting
confidence: 51%
“…Twenty-two articles were included in the final evidentiary table. Reasons for exclusion of fulltext articles included the absence of a valid comparison group (n = 14), [1][2][3][7][8][9][10]12,13,20,25,26,28,35 the absence of a valid outcome variable (n = 4), 14,18,22,32 invalid study design (n = 2), 30,31 and redundant patient population (n = 1) (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The majority of excluded papers did not include a comparison group or control group. [1][2][3][7][8][9][10]12,13,20,25,26,28,35 Other reasons for exclusion included invalid study design (questionnaire survey), 30,31 redundant patient population 5 (only the paper with the longest reported follow-up was included), and absence of a valid outcome variable (change in ventricle size, development of spinal canal stenosis, historical description, and frequency of hospital visits). 14,18,22,32 Conclusions recommendation: There is insufficient evidence to demonstrate an advantage of one shunt hardware design over another for the treatment of pediatric hydrocephalus.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…However, investigators have not agreed on a clearly superior valve when used in a broad range of children with hydrocephalus. 1,[7][8][9]12,13,16,[20][21][22]29,32 Conventional NPVs require surgeons to select an optimal opening pressure before implantation. Inaccurate estimates of the shunt valve function in situ may necessitate replacement of the valve to prevent over-or underdrainage.…”
mentioning
confidence: 99%
“…Rates of infection, type and frequency of shunt complications, and 2-year shunt survival curves have all shown no significant difference between the 2 types of valves. [7][8][9][10]13,20,21,24 Moritake et al 20 reported that PVs have a lower risk for a combination of postoperative infection with malfunction over a 3-month period than NPVs, but neither infection nor malfunction alone reaches significance.…”
mentioning
confidence: 99%